Tannic acid-reinforced methacrylated chitosan/methacrylated silk fibroin hydrogels with multifunctionality for accelerating wound healing. (1st November 2020) - He, Xi; Liu, Xuezhe; Yang, Jin; Du, Haibo; Chai, Ningwen; Sha, Zhou; Geng, Mengru; Zhou, Xiaojun; He, Chuanglong
Graphical abstract: Highlights: TA-reinforced CSMA/SFMA hydrogels with double-network were developed. TA-reinforced hydrogels exhibited enhanced mechanical properties. Adhesiveness, antibacterial and antioxidative properties were improved by TA treatment. TA-reinforced hydrogels significantly accelerated the wound healing process. Abstract: Natural polymeric hydrogel featuring multifunctional properties is more attractive as wound dressing. Herein, Tannic acid (TA)-reinforced methacrylated chitosan (CSMA)/methacrylated silk fibroin (SFMA) hydrogels were fabricated by two-step method of photopolymerization and TA solution incubating treatment. The TA in hydrogels not only served as second crosslinker improving the mechanical performance of up to a 5-fold increase (5 % TA treatment) than the pristine one, but also as functional molecule that endowed the hydrogels with enhanced adhesiveness and antioxidative properties. Besides, the introduction of TA into hydrogels further improved the antimicrobial activities against both Escherichia coli ( E. coli ) and Staphylococcus Aureus ( S. aureus ), as well as the cytocompatibility on fibroblasts. Moreover, it was demonstrated that the TA-treated CSMA/SFMA hydrogels could significantly promote wound healing in a full-thickness skin defect model. Collectively, these results showed that TA-reinforced CSMA/SFMA hydrogels could be a promising candidate as wound dressing.